BLENDED LEARNING IN TEACHING FOREIGN LANGUAGES - Barotaliyeva Muyassar Murodali qizi (American Journals Publishing, 2023)
At present, there is a prime focus on the fields of knowledge in which citizens acquire the skills and knowledge necessary for effective communication, e.g. on the teaching of foreign languages and ICT. Nevertheless, to combine and exploit both areas effectively, one (in this case a teacher) has to employ an appropriate methodology. Probably, the most suitable approach to the teaching of foreign languages with the help of ICT nowadays seems to be the so-called blended learning. Blended learning enables to use many different forms and methods in foreign language teaching. On-line courses leave room for any inclusion of many listening texts and video files. In order to facilitate the language study to students a lot of on-line courses of professional English, courses of area studies of English speaking countries, courses of professional German, courses for translators, written business English course and others have been prepared . These courses are based on tutors’ and students’ needs, students’ knowledge, on teachers’ long term experience, and of course on the positive attitude of ICT students (and not only of them) to modern technologies. Therefore, the aim of this paper is to emphasise the importance of blended learning for the teaching of foreign languages.
Keywords: foreign language teaching; ICT; foreign languages; teaching; blended learning; synchronous teaching; asynchronous teaching.